From Differences in Export Behavior of Services and Manufacturing Firms in Slovenia - Tanja Grublješič; Jože Damijan (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
We provide new comprehensive evidence on similarities and differences in export Behavior of Slovenian manufacturing and services firms by using detailed firm-level panel data for Slovenia. Main findings show that export Behavior in these two types of firms is similar and in line with the big picture that is by now familiar from the literature. Slovenian exporting services firms are more productive than non-exporting firms when observed and unobserved heterogeneity are controlled for. Export premia of services firms is even larger than for exporting manufacturing firms. Similarly, pre-entry premia over non-exporters is even larger than for manufacturing firms. We find some evidence of significant learning-by-exporting effects for services firms, but only when using the Levinsohn and Petrin measure of total factor productivity.
Keywords: 330; Trade in Services; Firm heterogeneity; Self-selection; Learning by exporting